2015
DOI: 10.11113/jt.v75.5242
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Elements of a Good City Planning: An Analysis of City Planning Theories

Abstract: Urban theory is fragmented. The relation of human purposeful activity (interaction) and city form is a major feature. However, some attention given to commentator's theory such as Jane Jacobs, Kevin Lynch and Alan Jacobs and Donald Appleyard in their taught toward city planning, in which the theories that explain the city planning's idea are reviewed. This study investigates comparison of ideology and theory of city planning. In order to search for the city planning theory, a qualitative method research which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Increased runoff from impermeable surfaces causes substantial flooding, severe stream erosion, decreased groundwater recharge, and fish habitat deterioration. These impermeable surfaces can convey many toxins accumulating in metropolitan areas, such as fertilizers, silt, pathogens, pesticides, and chloride (Selbig, 2018, Safee et al, 2015. To avoid flooding, stormwater runoff must be directed appropriately and effectively in the urban environment.…”
Section: Introductionmentioning
confidence: 99%
“…Increased runoff from impermeable surfaces causes substantial flooding, severe stream erosion, decreased groundwater recharge, and fish habitat deterioration. These impermeable surfaces can convey many toxins accumulating in metropolitan areas, such as fertilizers, silt, pathogens, pesticides, and chloride (Selbig, 2018, Safee et al, 2015. To avoid flooding, stormwater runoff must be directed appropriately and effectively in the urban environment.…”
Section: Introductionmentioning
confidence: 99%
“…Safee et al [17] defined seven planning factors to develop the metro station catchment area: (1) Community Life, (2) Sense and Identity of the Place, (3) Livability, (4) Sidewalk Pedestrian, (5) Built Environment Connection, (6) Density Size, and (7) Environment. The urban planners concluded that different metro station catchment areas have similar development characteristics in reference to these factors, and these similarities lead to understanding the urban planning context and proposing different typologies of development [18,19].…”
Section: Introductionmentioning
confidence: 99%